DFT Calculations of Vibrational Frequencies of Aluminum and Phosphorous Doped-Carbon Clusters - Ahmad Malik, Maqsood; Nabi, Firdosa; G. Jesudason, Christopher; Ahmed Al-Thabaiti, Shaeel (Asian Journal of Chemistry, 2013)
We have designed numerous models of aluminum (CnAlm) and phosphorus (CnPm) doped carbon clusters (n = 3 and m = 4). The geometry optimization, bond length and calculation of vibrational frequency were carried out in each case by DFT in local density approximation. We also try other widely used functionals but local density approximation functional works well in our study. Numerous cluster structures of aluminum and phosphorus were prepared because of their different bonding preference. In addition, the total energies of the CnAlm and CnPm clusters were also discussed.